2006
DOI: 10.1088/0967-3334/28/1/003
|View full text |Cite
|
Sign up to set email alerts
|

Snoring noise pollution—the need for objective quantification of annoyance, regulatory guidelines and mandatory therapy for snoring

Abstract: Habitual snoring without episodes of apnea or hypoventilation and without respiratory related arousals is considered to be annoying and without any need for treatment. However, studies seem to suggest an enormous psychosocial impact of annoyance for the bed partner. Apart from subjective questionnaires there still exists no generally accepted mode of measurement that can describe snoring objectively. We therefore adapted methods developed for environmental medicine and established a new snore score using psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 47 publications
2
9
0
Order By: Relevance
“…A L10 value of 45 dB(A) was exceeded by 49.5% of the cases. This is the same with Caffier et al's [14] study, in which the LAeq maximum was 47dB(A), which greatly exceeded the recommended emission levels from the WHO noise guidelines. Loud snoring sound could influence the quality of sleep for both snorer and bed partner.…”
Section: Multiple Linear Regression Analysessupporting
confidence: 89%
“…A L10 value of 45 dB(A) was exceeded by 49.5% of the cases. This is the same with Caffier et al's [14] study, in which the LAeq maximum was 47dB(A), which greatly exceeded the recommended emission levels from the WHO noise guidelines. Loud snoring sound could influence the quality of sleep for both snorer and bed partner.…”
Section: Multiple Linear Regression Analysessupporting
confidence: 89%
“…They have to be diVerentiated from the regular respiratory sounds, which is not diYcult for the human brain [6]. But there is an urgent need to Wnd a generally accepted deWnition of snoring sounds by physical measured values, which has not yet been fulWlled [16]. The reason for this is particularly the lack of standardized measurement methods: contact microphones are used as well as free hanging microphones, but at diVerent distances from the patients.…”
Section: Discussionmentioning
confidence: 99%
“…CaYer et al [16] developed the "Berlin snore score" for this purpose. This is calculated, with diVerent weighting, from the sound pressure levels with correction factors or their percentile values and the snoring time to give a score of between 0 and 100.…”
Section: Table 1 Correlationsmentioning
confidence: 99%
“…Based on the dataset of 13 snore sound samples and sample size of 25 listeners, the diagnostic accuracy was quantified using ROC curves [155][156][157] and notched box plots [139,140,181,182] Moreover, the typical threshold separating these two diagnostic classes of snore sounds falls on the rating of 4 (neutral response), except for the metric of annoyance whose threshold is 5, emphasizing that snoring is often considered as a nuisance. A study on 37 consecutive snoring men has found that 55% of their bed partners are irritated by snoring, and 40% of them chose to sleep in a separate room more than once a week in order to get a more restful and recuperative sleep [246], negatively affecting their partners' health and well-being [105,247,248]. Other studies have further reported the devastating consequences of snore-induced noise pollution on couple's relationship, for example, marital strife, divorces, and attempted murder [249][250][251].…”
Section: Statistical and Exploratory Data Analysismentioning
confidence: 99%
“…In spite of the UA inherent intricacy, it can be regarded as a concatenation of cylindrical sections whose lengths are shorter than 1/8th the acoustic wavelength of interest [158,159,266]. With the maximum frequency of interest for snore signals as 5000 Hz [99,105] and the speed of sound for moist air at 37ºC as 35400 cm/s, the account for energy loss and mass inertia of air. The UA acoustic transfer function can be ultimately described by the product of all section transfer matrices.…”
Section: Upper Airway Acoustic Modelingmentioning
confidence: 99%